PEMANFAATAN TOKO BUKU ONLINE UNTUK MENINGKATKAN LAYANAN DISTRIBUSI BAHAN AJAR BAGI MAHASISWA UNIVERSITAS TERBUKA - Pardamean Daulay (LPPM Universitas Terbuka, 2010)
One of the weaknesses of UT as the holder of distance education is the difficulty in distributing the printed learning materials (modules) to the students spread all over the country. Recently, UT has developed Online based module distribution which is commonly known as UT E-bookstore (TBO-UT). This research is to describe the effectivity of using TBO-UT, and done by qualitative approach and quantitative approach. The result of this research shows that (1) the students participation in using TBO-UT is still low, which is only 10,36% from all students of UBJJ-UT Surabaya. It implies that (a) the TBO is still new that not all students know about it (b) less socialization of using TBO-UT (c) the low skill of students in accessing the internet. This research also shows that Online based module distribution is not effective yet to fulfill the students needs. It is caused by some factors (a) the module distribution is not on time yet (b) the students find difficulty in paying the modules for no Bank Mandiri in their area (c) the bad connection in accessing the UT website (d) the lack of modules needed by students. The presence of TBO UT really helps full time worked students but becomes a problem for those who get difficulty in accessing the internet.